2016
DOI: 10.1177/0022034516651823
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of the Growth Plate and Cranial Synchondrosis

Abstract: Long bones and the cranial base are both formed through endochondral ossification. Elongation of long bones is primarily through the growth plate, which is a cartilaginous structure at the end of long bones made up of chondrocytes. Growth plate chondrocytes are organized in columns along the longitudinal axis of bone growth. The cranial base is the growth center of the neurocranium. Synchondroses, consisting of mirror-image growth plates, are critical for cranial base elongation and development. Over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 59 publications
5
77
0
1
Order By: Relevance
“…Elevated ROS in growth plates of mice has previously been shown to disrupt the columnar proliferation of chondrocytes and their hypertrophic differentiation (Morita et al, 2007). Our data suggests that in addition to ROS-mediated effects on chondrogenesis, indirect, non-ROS mediated effects of chronic alcohol consumption on growth hormone/IGF-1 signaling (Badger et al, 1993; Srivastava et al 2002; Wang et al 2004); the calcium/Vitamin D axis (Shankar et al 2008a, Mercer et al, 2012) or effects on regulation of local growth factors in the growth plate such as Indian hedgehog, FGFs, or BMPs (Wei et al 2016) may also significantly impact bone lengthening.…”
Section: Discussionmentioning
confidence: 83%
“…Elevated ROS in growth plates of mice has previously been shown to disrupt the columnar proliferation of chondrocytes and their hypertrophic differentiation (Morita et al, 2007). Our data suggests that in addition to ROS-mediated effects on chondrogenesis, indirect, non-ROS mediated effects of chronic alcohol consumption on growth hormone/IGF-1 signaling (Badger et al, 1993; Srivastava et al 2002; Wang et al 2004); the calcium/Vitamin D axis (Shankar et al 2008a, Mercer et al, 2012) or effects on regulation of local growth factors in the growth plate such as Indian hedgehog, FGFs, or BMPs (Wei et al 2016) may also significantly impact bone lengthening.…”
Section: Discussionmentioning
confidence: 83%
“…Harris’ hematoxylin (VWR, Radnor, PA, 10143–606) and Eosin (VWR, 95057-848) staining proceeded by standard protocol. As the SOS is the last synchondrosis of the cranial base to fuse in humans, it is assumed that it has a greater impact on craniofacial development, thus we have focused on this region [12]. Three sections at least 30 μm apart were used for histomorphometric analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These same processes are important for the craniofacial skeleton, as the synchondroses of the cranial base, like the growth plate in long bones, contribute to elongation by proliferation and hypertrophy of chondrocytes. Unlike long bone growth plates, the synchondroses produce growth in opposing directions [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Prior research studies have demonstrated that long bones are formed through endochondral ossification of chondrocytes in which col2a1 is one of the most requisite matrix collagens (30). Thus, we hypothesized that the inhibition of BET bromodomain proteins may also affect the growth of the organism.…”
Section: I-bet151 and (ϩ)-Jq1mentioning
confidence: 95%